Childhood emotional abuse, physical abuse, and neglect are associated with theory of mind decoding accuracy in young adults with depression. (October 2018) - Rnic, Katerina; Sabbagh, Mark A.; Washburn, Dustin; Bagby, R. Michael; Ravindran, Arun; Kennedy, James L.; Strauss, John; Harkness, Kate L.
Highlights: In the depressed group, emotional abuse was related to poorer theory of mind decoding. In the non-depressed group, physical abuse was related to poorer theory of mind decoding. Those reporting neglect showed better theory of mind decoding than those without. Abstract: The current study is the first to examine the relation of childhood abuse and neglect history to theory of mind decoding accuracy as moderated by depression. Fifty-five young adults with current or lifetime unipolar depression diagnosis and 70 never-depressed young adults completed the 'Reading the Mind in the Eyes task, ' (RMET). Childhood emotional abuse, physical abuse, and neglect were assessed with a gold-standard contextual interview with standardized, independent ratings. Poorer RMET accuracy was associated with a history of emotional abuse in the depressed group and a history of physical abuse in the non-depressed group. In contrast, across both groups, those with a history of neglect showed significantly enhanced theory of mind decoding accuracy compared to those without. Further, differential accuracy across positive, negative, and neutral valenced stimuli in the RMET was observed in each model. These findings indicate that distinct theory of mind performance results from early experiences of threat versus deprivation, and suggest that early intervention may be most successful in preventing negative interpersonal outcomes of maltreatment by focusing on remediating theory of mind deficits resulting from abuse, and tempering heightened sensitivity in those exposed to neglect.